References (Scottish Historical and Archaeological Internet Reports, 2025)
In 2013 excavation works were undertaken at the location of the former Canongate Charity Poorhouse (or workhouse) on the New Waverley development site, at the junction of Calton Road and Old Tolbooth Wynd, Canongate, Edinburgh. The excavation revealed development of the site from the initial cultivation of the ‘backlands’ in the 12th/13th centuries to the construction of the Poorhouse in 1761.A sequence of buried garden soils/middens relating to pre-18th-century activity was recorded, in addition to the remains of a single burgage plot boundary and associated rig and furrow deposits. Substantial structural features related to the 18th-century Poorhouse were revealed, including sandstone walls with wooden plank and pinion foundation rafting. Seven burials of probable late 17th-/early 18th-century date associated with the Canongate Kirk were recorded along the site’s southern boundary (an eighth had been encountered in 1997).A rich artefact and ecofact assemblage was recovered from the soils and midden deposits, including imported fine glassware. The ceramic assemblage included Scottish White Gritty Ware (SWGW), Scottish Post-medieval Reduced Ware (SPMRW) and Scottish Post-medieval Oxidised Ware (SPMOW), together with high-status imported material such as a Spanish gaming piece and a rare German stove tile.Consumption patterns revealed by the artefact evidence appear to reflect the high status of the Canongate’s inhabitants prior to the greater development of the site during the 18th century. The creation of the Poorhouse stands in stark contrast to this, revealing the changing fortunes of this part of post-medieval Edinburgh.